Radiological characterization of ITER materials - Kourgiantakis, Rafail; Vasilopoulou, Theodora; Diakaki, Maria; Kokkoris, Michael; Savva, Marilia I.; Stamatelatos, Ion-Evangelos (HNPS Advances in Nuclear Physics, 2024)
Samples of ITER materials were irradiated at the Joint European Torus (JET) to study their activation properties under neutron irradiation in a real fusion environment. The samples were irradiated at JET during the 2021 Tritium-Tritium (T-T) and Deuterium-Tritium (D-T) plasma experimental campaigns, with neutron flux levels and energy spectra comparable to the ones expected at ITER, and then distributed to European labs for gamma-spectroscopic measurements. In this work, the methodology of gamma-spectroscopic analysis performed at NCSRD is presented. The activated samples were measured using a high purity germanium detector to identify the produced radionuclides and quantify their induced activity levels. Correction factors, calculated using the MCNP code and the TrueCoinc program, were applied to account for the effects of self-attenuation of photons within the sample and true-coincidence summing in the detector, respectively. This work provides experimental data on the activation properties of materials used in ITER, which is important for the radiation protection of personnel and the safe handling of activated reactor components during maintenance activities, as well as for the decommissioning planning of ITER materials and their safe disposal as waste or for recycling.